Search for new resonances decaying to a W or Z boson and a Higgs boson in the;bb¯ ;bb¯, and ¯bb¯ channels with pp collisions at s;=13 TeV with the ATLAS detector - Aaboud, M. (2016)
A search is presented for new resonances decaying to a W or Z boson and a Higgs boson in the ℓ + ℓ −bb¯, ℓνbb¯, and νν¯bb¯ channels in pp collisions at √ s = 13 TeV with the ATLAS detector at the Large Hadron Collider using a total integrated luminosity of 3.2 fb−1 . The search is conducted by looking for a localized excess in the WH/ZH invariant or transverse mass distribution. No significant excess is observed, and the results are interpreted in terms of constraints on a simplified model based on a phenomenological Lagrangian of heavy vector triplets.